MODEL PEMBELAJARAN KEDWIBAHASAAN MURID SD BERBASIS ANALISIS KONTRASTIF - Hasmawati, Hasmawati Hasmawati; Yunus, Andi Fatimah; Mantasiah, Mantasiah Mantasiah (Indonesian Journal of Educational Studies, 2010)
Abstract. Bilingual Instruction Model for Elementary Students Based on Contrastive Analysis. This study aims at (1) developing a learning model guide book, (2) developing a set of instructional devices, (3) describing student learning outcomes as a result of the implementation of contrastive analysis model, and (4) describing the effectiveness of contrastive analysis model. The results showed that the student learning through contrastive analysis model—experimental treatment increased. The average score of the experimental class is significantly higher than the control class (p<.05). This contrastive analysis-based model of bilingual instruction at elementary school effectively minimizes the occurrence of interference in student essays. Abstrak. Model Pembelajaran Kedwibahasaan Murid SD Berbasis Analisis Kontrastif. Penelitian ini bertujuan (1) mengembangkan buku panduan model pembelajaran, (2)  mengembangkan  perangkat  pembelajaran, (3) mendeskripsikan  hasil belajar  murid  sebagai dampak pelaksanaan  model analisis kontrastif, (4) mendeskripsikan  keefektifan model  analisis  kontrastif.  Hasil   penelitian  menunjukkan  hasil  belajar  murid  melalui model  analisis  kon-trastif  mengalami peningkatan.  Skor  rata-rata pada  kelas  eksperimen  lebih tinggi dari  pada  kelas kontrol, yaitu 52,53 berbanding 66,22. Hasil  analisis uji-T menunjukkan  adanya  perbedaan  yang signifikan  antara  hasil belajar  murid pada kelas  eksperimen  dan kelas kontrol.  Model pembelajaran  kedwibahasaan  murid SD  berbasis analisis  kontrastif  efektif  meminimalkan  terjadinya  interferensi  pada  karangan  murid. Kata  kunci: pembelajaran kedwibahasaan, analisis kontrastif